The Expressive Utterances Found in the Song Love You Like A Love Song by Selena Gomez - Suryaningsih*, Rah Tri; Musyarofah, Lailatul; Putranto, Henry Rio (Universitas Syiah Kuala, 2024)
The study discussed the analysis of expressive utterences found in the lyrics of the song